Optimum Wire Busbar Design by Genetic Algorithm - Ante Marušić (Tehnički Vjesnik, 2019)
This work shows genetic algorithm approach to the optimum wire busbar design. Parameters of the wire busbar are mapped into a chromosome like a string. This includes insulator string type, wire conductor type and number, bundle wire conductor distance, rigid spacer number, phase distance, wire conductor nominal stress, 3D truss L elements types and foundation type. GA uses natural selection on a population of such strings. The fitness function is the wire busbar price. GA performance is presented on one example with variation of input data – nominal current, short-circuit current and short-circuit duration.